Modelamento matemático do processo de soldagem GMAW - Ivan Jose de Santana (2010)
This thesis describes the development and validation of a mathematical model that describes the electrical and operational behavior of GMA welding. Initially it was developed a static model that was able to simulate welding conditions characterized by small current and tension variation usually found with free-flight metal transfer. Afterwards, a dynamic model capable to simulate abrupt current and voltage changes usually observed in short-circuit welding was developed. These models were based on aset of equations that describes the power source characteristics, the voltage drop along the electric arc and the welding circuit and the energy balance on the wire tip. Despite the large number of variables of GMA welding and the complex relation among them, the results from the models agreed well with data from the literature and to experimentalresults. The dynamic model was able to simulate the welding parameters values (with less 10% of error) and to predict transitions in metal transfer mode. The mean current and voltage and their waveform variation, arc length, short circuit frequency and metal transfer transition were obtained as a function of wire feed rate, contact tip-to-work distance and open circuit voltage. The results indicate that the developed models,specially the dynamic one, are able to estimate welding parameters for specific welding conditions and can contribute to a more fundamental understanding of this welding process.